2014
DOI: 10.1038/nmat3889
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical memory and dosing influence stem cell fate

Abstract: We investigated whether stem cells remember past physical signals and whether these can be exploited to dose cells mechanically. We found that the activation of the Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding domain (TAZ) as well as the pre-osteogenic transcription factor RUNX2 in human mesenchymal stem cells (hMSCs) cultured on soft poly(ethylene glycol) (PEG) hydrogels (Young’s modulus E ~ 2 kPa) depended on prior culture time on stiff tissue culture polystyrene (TCPS; E ~ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

50
985
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 962 publications
(1,038 citation statements)
references
References 31 publications
50
985
1
2
Order By: Relevance
“…Recent investigations have shown that YAP/TAZ behaves as cellular rheostats, which largely influence mechanosensing and affect cell function and fate 2, 40. For hMSCs in elastic hydrogels, YAP/TAZ mainly remained in the cytoplasm throughout the 7 d culture (Figure 5a,f and more representative images in Figure S11, Supporting Information), reminiscent of previous findings in slowly relaxing9 or nondegradable gels 38.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Recent investigations have shown that YAP/TAZ behaves as cellular rheostats, which largely influence mechanosensing and affect cell function and fate 2, 40. For hMSCs in elastic hydrogels, YAP/TAZ mainly remained in the cytoplasm throughout the 7 d culture (Figure 5a,f and more representative images in Figure S11, Supporting Information), reminiscent of previous findings in slowly relaxing9 or nondegradable gels 38.…”
supporting
confidence: 78%
“…By incorporating various biochemical, biophysical, and mechanical cues into a single system, hydrogels provide a powerful in vitro model to probe and understand the fundamentals of cell‐niche interactions2 and to provide information for testing hypotheses related to developmental and disease‐related processes 3, 4…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell morphology after 3 h of culture was very similar, and cells presented a well-developed actin cytoskeleton with tension fibres (Figure 4g) typical of cells cultured on 2D rigid substrates [51] (stiffness measured via indentation with the AFM was 3.417 ± 1.037 GPa for PLLA and 3.027 ± 0.760 GPa for PLLA/ZnO, Figure S3). Cell shape descriptors were calculated and shown in Figure 4h.…”
Section: Figure 4amentioning
confidence: 94%
“…[ 3,4 ] Material systems that mimic the natural niche environment of MSCs may offer an alternative to the use of complex cocktails of soluble factors used in the culture media. Previous studies show that the cell/material interface plays an essential role on MSC function and differentiation, encompassing promising approaches to manipulate differentiation of stem cells ranging from chemistry, [5][6][7] surface modifi cations, [ 8,9 ] topography, [10][11][12] stiffness, [ 13,14 ] and even dynamic material properties such as stress relaxation. [ 15 ] While we are starting to identify the range of materials properties that can be used to drive stem cell differentiation, there is much left to discover and understand.…”
mentioning
confidence: 99%